Motivação, valor instrumental e percepção de suporte: um modelo preditor de impacto do treinamento - Santos, Tiago Regis Cardoso (2012)
The aim of this study was investigate the relationship between the Training Impact at Work, the dependent variable, and the set of individual variables, Motivation to Learn, Motivation and Value Transfer Instructional Training (divided into Relevance and Utility) and the contextual variable Perceived Organizational Support in 95 participants. |Results of Pearson\'s r indicated that the impact correlates with the Motivation to Learn, with Utility and Importance. Already a stepwise multiple regression analyzes indicated that the Importance and Motivation Learning together explain 14% of the variance of Impact, and the Motivation to Transfer, Utility and Perceived Organizational Support were not predictive. Two groups were divided based in Engagement Initiative in Training: 1) engaged by their own initiative, and 2) engaged by company\'s request. Comparing the averages of group‟s with t student, group 1 realized greater Utility, and lower Importance and Perceived Organizational Support than second group. Therefore planned trainings must be conducted considering predictor variables, providing specific support for training. New studies about the characteristic Engagement Initiative in Training are suggested because it seems to be an important explanation for the results of Importance and Usefulness of Training in this sample.